Perbedaan Penggunaan Jenis Media Filtrasi Pasir dengan Karbon Aktif terhadap Penurunan Fe (Besi) Air Sumur Gali di Dusun Sidomulyo, Trimulyo, Sleman - Dena Kurnia Isradaningtyas; Tuntas Bagyono; Herman Santjoko (Sanitasi: Jurnal Kesehatan Lingkungan, 2018)
Water is the most essential need for people to fulfill their daily needs. Residents in SidomulyoHamlet, of Trimulyo Village, in Sleman District, use dug wells as the primary source of clean water supply. However, the water quality gained is low because of high iron content in it. The studywas aimed to determine the differences between sand and activated carbon as filtration mediafor decreasing Fe concentration, by conducting a “pre-test post-test with control group” designedexperiment with five replications. The study results showed that sand media was able reduce theFe in average of 1.18 mg/l, while with activated carbon media it was 1.27 mg/l, and in the controlgroup it was 0.4 mg/l. The analysis of one way anova test at 95 % confidence level obtained pvalue <0,001, which means that the differences is significant. To conclude, to decrease the Fecontent in Sidomulyo Hamlet, the well water can be processed by filtration, either with sand oractivated carbon. Nonetheless, activated carbon media is proved more effective.